2023
DOI: 10.3389/fpls.2023.1242025
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey and characterization of microsatellites in cashew and design of a web-based microsatellite database: CMDB

Siddanna Savadi,
B. M. Muralidhara,
V. Venkataravanappa
et al.

Abstract: The cashew is an edible tree nut crop having a wide range of food and industrial applications. Despite great economic importance, the genome-wide characterization of microsatellites [simple sequence repeats (SSRs)] in cashew is lacking. In this study, we carried out the first comprehensive genome-wide microsatellites/SSRs characterization in cashew and developed polymorphic markers and a web-based microsatellite database. A total of 54526 SSRs were discovered in the cashew genome, with a mean frequency of 153 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…In terms of SSR analysis, our study identified a substantial number of SSRs, amounting to 2,761,190, with variable densities in the tested genomes. The prevalence of Class II SSRs (shorter than 20 bp), characterized by shorter motifs, was consistent with the previous findings in plants [37][38][39]. Furthermore, the dominance of AT-rich SSR motifs aligns with similar observations in Musa and other plant species [40][41][42].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of SSR analysis, our study identified a substantial number of SSRs, amounting to 2,761,190, with variable densities in the tested genomes. The prevalence of Class II SSRs (shorter than 20 bp), characterized by shorter motifs, was consistent with the previous findings in plants [37][38][39]. Furthermore, the dominance of AT-rich SSR motifs aligns with similar observations in Musa and other plant species [40][41][42].…”
Section: Discussionsupporting
confidence: 91%
“…Molecular markers are particularly useful in crops with long breeding cycles or complex traits that are difficult to measure directly. The availability of whole genome sequences has enabled the development of various types of molecular markers and the creation of molecular marker databases to maximize their utility [37]. In this study, a novel molecular marker database was developed from the whole genome sequences, EST, and GSS sequences of 13 Musa species.…”
Section: Discussionmentioning
confidence: 99%